Prove that for $x>y>0$ $$\sqrt {xy} <\frac {x-y}{\ln x-\ln y}<\frac {x+y}2$$ Using $x=y+k$, we can turn the inequality into $$\sqrt{y^2+ky}<\frac k{\ln(1+\frac ky)}<y+\frac k2$$ Now what do i do to the $\ln\left(1+\frac ky\right) $ term? We can't approximate it using the expansion of $\ln(1+x)$ as we have no information on $k$, i.e., how big $x$ is in comparison to $y$. Please give a hint.


Hint: Make the substitution: $t = \dfrac{x}{y} > 1$, then the inequality you need to prove:

$$t^{1/2} \le \dfrac{t - 1}{\ln t} \le \frac{1+t}{2}$$

You can take their difference as a function of $t$, compute their derivative and show they are positive. You can see here for example.


For $ 0<a<b$ note $ A(a,b)=\frac{a+b}{2}, G(a,b)=\sqrt{ab}, L(a,b)=\frac{b-a}{\ln b-\ln a}$

Proof 1.:

With $\frac{b}{a} = x > 1$ we have: $\sqrt{x}< \frac{x - 1}{\ln x} < \frac{1}{2}( x + 1)$

Let functions $f, g : [ 1, \infty) \rightarrow \textbf{R}$: $f( x ) = \ln x -\sqrt{x}+ \frac{1}{\sqrt{x}}, g( x ) = \ln x - \frac{2(x-1)}{x+1}$

with $f'( x ) = -\frac{(\sqrt{x}-1)^2}{2x\sqrt{x}}, g'( x ) = \frac{(x -1)^2}{x(x+1)}$ and $f(x) < 0 < g( x ),(\forall )x > 1 $.

Proof 2.:

Let $ H_{a,b}( x ): [ 0, 1 ]\rightarrow \textbf{R}$, $H_{a,b}( x ) = \frac{1}{2}( a^x.b^{1-x} + a^{1-x}.b^x )$ with $ L( a,b ) = \int^{1}_{0}H_{a,b}( x )dx, $ $H_{a,b}( 0 ) = H_{a,b}( 1 ) = A( a, b)$ and $H_{a,b}( \frac{1}{2} )= G( a, b ).$

$H^{'}_{a,b}( x ) = \frac{1}{2}( a^x.b^{1-x} - a^{1-x}.b^x )\ln \frac{b}{a}$ implies $G( a, b ) \leq H_{a,b}( x ) \leq A( a, b),(\forall) x\in [ 0, 1 ].$

In what follows we use other depictions of logarithmic mean using integral:

$\frac{1}{L( a, b )} = \frac{1}{b - a}\int^{b}_{a}\frac{dx}{x}=\frac{1}{b - a}\int^{\frac{b}{a}}_{1}\frac{dx}{x}$

$\frac{1}{L( a, b )} = \int^{1}_{0}\frac{dx}{xa + ( 1- x )b}$

$\frac{1}{L( a, b )} = \lim_{x\rightarrow 0}\int^{x}_{0}\frac{dt}{(t + a)( t + b )}$

Proof 3.:

For $(\forall)x > 0$ we have: $\frac{2}{(x+1)^2}\leq\frac{1}{2x}\leq\frac{x+1}{4x\sqrt{x}}$

Integrating this inequality from $1$ to $\frac{b}{a}$ now obtain :

$\frac{b-a}{b+a}\leq\frac{1}{2}ln\frac{b}{a} \leq\frac{b-a}{2\sqrt{ab}}...$

Proof 4.:

For $(\forall)x \geq 0$ we have:

$x^{2} + 2x\sqrt{ab} + ab \leq x^{2} + x(a + b) + ab \leq x^{2} + x(a + b) + (\frac{a + b}{2})^2$

Reversing these inequalities and integrating them using last representation is obtained inequality.

Proof 5.:

Noting $a = e^{x}, b = e^{y}$ demonstrated inequality may be written as

$e^{\frac{x+y}{2}} \leq \frac{e^y - e^x}{y - x} \leq \frac{e^x + e^y}{2}.$

Dividing this inequality with $e^{\frac{x+y}{2}}$the first part to write:

$1\leq \frac{e^{\frac{y - x}{2}} - e^{\frac{x - y}{2}}}{y - x}\Longleftrightarrow \frac{y - x}{2} \leq \sinh\frac{y -x}{2}$ true that $t \leq \sinh t,( \forall) t\geq 0.$

Similarly, the second part is reduced to $t \geq \tanh t,( \forall) t\geq 0.$

Proof 6.:

Inequality in the previous proof can be obtained by applying Hadamard-Hermite's inequality function $f: \textbf{R}\rightarrow \textbf{R}, f( x ) = e^{x}$

(Hadamard-Hermite's inequality: $f ( \frac{a + b}{2} )\leq\frac{1}{b - a}.\int^{b}_{a}f( x ) dx \leq \frac{f ( a ) + f ( b )}{2}.$)

Inequality of utterance can be demonstrated using CBS with integrals of convenient functions chosen.

Proof 7.:

If $f:[a, b]\rightarrow(0, \infty)$ then

$\int^{b}_{a}(\sqrt{f(x)})^2dx.\int^{b}_{a}\frac{1}{(\sqrt{f(x)})^2}dx\geq(\int^{b}_{a}(\sqrt{f(x)})^2.\frac{1}{(\sqrt{f(x)})^2}dx)^2$ and

$\int^{b}_{a}f(x)dx.\int^{b}_{a}\frac{1}{f(x)}dx\geq (b-a)^2.$

Now for $f(x)=\frac{1}{x}$ we have $(\ln b-\ln a).\frac{b^2-a^2}{2}>(b-a)^2$ ie $L ( a, b )\leq A(a, b).$

For $f(x)=e^x$ is obtained $(e^b-e^a)(e^{-a}-e^{-b})>(b-a)^2$ and noting $a=\ln x, b=\ln y$ cu $0<x<y$ result $G(x,y)< L(x,y).$

Prof 8.:

If $f:[a, b]\rightarrow(0, \infty)$ then $\int^{b}_{a}(f(x))^2dx.\int^{b}_{a}1dx\geq(\int^{b}_{a}f(x).1dx)^2$ or $(b-a)\int^{b}_{a}(f(x))^2dx\geq(\int^{b}_{a}f(x)dx)^2.$ Now, applying this inequality for $f(x)=\frac{1}{x}$ is obtained

$(\ln b- \ln a)^2<(b-a)(\frac{1}{a}-\frac{1}{b})$ from which it follows that $G(a,b)< L(a,b).$

For $f(x)=\frac{1}{\sqrt{x}}$ rezult $4(\sqrt{b}-\sqrt{a})^2<(b-a)(\ln b-\ln a).$ Noting $\sqrt{b}=y$ and $\sqrt{a}=x$ we have $4(y-x)<2(y^2-x^2)(\ln y-\ln x)$and finally $L(x,y)<A(x,y).$

(Paper presented at the XVIII Conference of the Mathematical Society of Romania, Iasi, 24 -26 October 2014)

  • $\begingroup$ wow ! (+1) :D Awesome !! proofs $(7)$ is new to me ! Never thought about it like that :D $\endgroup$ – r9m Dec 29 '14 at 15:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.